2018
DOI: 10.1111/ajco.13034
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of exemestane therapy on bone mineral density supported by bisphosphonates: Results of 5‐year adjuvant treatment in postmenopausal women with early‐stage breast cancer

Abstract: Oral Bis improves BMD of the FN in patients with osteoporosis. Five-year EXE treatment with proper addition of Bis helps maintain the BMD of the LS and FN at the sixth year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Real-world studies show that in terms of bone loss, steroidal AI is expected to be superior to nonsteroidal AI because steroids in bone would be favorable for bone metabolism. In an observational study, exemestane treatment maintained BMD of femoral neck (FN), suggesting that exemestane is favorable for BMD of FN [ 52 ]. The reason why steroidal AI induces less damage to FN compared with nonsteroidal AI is unknown, but steroidal AI might affect bone turnover directly through its structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-world studies show that in terms of bone loss, steroidal AI is expected to be superior to nonsteroidal AI because steroids in bone would be favorable for bone metabolism. In an observational study, exemestane treatment maintained BMD of femoral neck (FN), suggesting that exemestane is favorable for BMD of FN [ 52 ]. The reason why steroidal AI induces less damage to FN compared with nonsteroidal AI is unknown, but steroidal AI might affect bone turnover directly through its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Oesterreich et al [ 53 ] reported that urine N-telopeptide concentration was significantly increased in patients treated with exemestane but not in those treated with letrozole[ 54 ]. Another observational study in a real-world setting, conducted with everolimus plus exemestane in postmenopausal women with hormone receptor-positive, HER2-negative advanced BC showed that this combination had lower incidents of bone-related events [ 52 ].…”
Section: Discussionmentioning
confidence: 99%